PENGARUH PENGUNGKAPAN INTELLECTUAL CAPITAL TERHADAP MARKET CAPITALIZATION PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008 DAN 2012 - Emalia Rachmi; Didik Ardiyanto (Diponegoro Journal of Accounting, 2014)
The aim of this study is to examine the influence of intellectual capital disclosure consist of human capital, structural capital, and relational capital on market capitalization. Book value, firm size, net profit, and leverage report used as control variable. The differences between this study with the other study are intellectual capital items, objects of study, and years of study. The item of the study has 61 items based on Li et al., company object is manufacture because there is so many kind of manufacturing industries which need higher level intellectual capital to improve the advantage in competition. The use of year 2008 and 2012 because PSAK number 19 was revisied at the end of 2009 so there was an one year a interval time to know the effect before the revision and it can be effective at January 1th, 2011. So, there was one year interval time to know the effect after revisied. This reason based on previous paper but different year with the standard released.           The population in this study consists of all listed manufacturing firm in Indonesia Stock Exchange in year 2008 and 2012. Sample was selected using purposive sampling method. A criterion for manufacturing firm which include of basic industry and chemicals, other industries, and consumer goods it’s easy to take annual report in website www.idx.co.id and have positive equity in year 2008 and 2012. Total data of this study is 96 data for two years. Multiple regression analysis used to be analysis technique.            The empirical result of this study show that intellectual capital disclosure (human capital, structural capital, and relational capital) have positively significant influenced on market capitalization in both years 2008 and 2012. Hopely, this result can encourage the firms to disclose intellectual capital it usefull to improve value of company with doing something positive like training for employee and research and development. Thus, it can make the investors know the value process creation so it can decrease asimetric information and increase market capitalization.